OCCUPATIONAL ACCIDENT RISK ANALYSIS IN IMAGAWAYAKI PRODUCTION USING THE HIRARC METHOD - Auliya Zahra Salsabila Lanipi; Muhammad Sabri Syahrir; Andi Ferina Herbourina Bonita; Stefiani Bengan Laba (Yayasan Adra Karima Hubbi, 2026)
Company Z is a frozen food processing industry located in Japan that produces imagawayaki cakes, traditional Japanese cakes that have a round shape and are filled with various fillings. In the production process, workers often come into direct contact with various large-capacity machines, raw materials, and work equipment that have potential hazards from a physical, mechanical, and ergonomic perspective. Some potential hazards often found in the production environment in this food industry include slippery floors due to water or oil spills, hot molds and baking machines, hot room temperatures, and the use of sharp tools. This study aims to identify all hazards in each stage of the production process, then map them into risk levels so that appropriate controls can be provided for existing risks. This study uses a descriptive quantitative approach that applies the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method as an analytical tool to identify potential hazards and assess the risk of work accidents in the food processing industry sector. Thus, the risk percentage results obtained are at extreme risk of 0%, high risk of 66%, medium risk of 27%, and low risk of 7%. There are also 50 risk control suggestions based on the risk control hierarchy, namely 2 elimination, 7 substitution, 12 engineering controls, 15 administrative controls, and 14 use of personal protective equipment.